Poly[1,4-bis(ammoniomethyl)cyclohexane [di-μ-iodido-diiodidoplumbate(II)]] - Rayner, Matthew Kyle (International Union of Crystallography, 2010)
The title compound, {(C(8)H(20)N(2))[PbI(4)]}(n), is an inorganic–organic hybrid. The structure is composed of alternate layers of two-dimensional corner-sharing PbI(6) octahedra ([Image: see text] symmetry) and 1,4-bis(ammoniomethyl)cyclohexane cations ([Image: see text] symmetry) extending parallel to the bc plane. The cations interact with the inorganic layer via N—H⋯I hydrogen bonding in the right-angled halogen sub-type of the terminal halide hydrogen-bonding motif.